On following pages: 36. Nelson's Collared Lemming (Dicrostonyx nelsoni); 37. Ogilvie Mountains Collared Lemming (Dicrostonyx nunatakensis); 38. Richardson's Collared Lemming (Dicrostonyx richardsoni); 39. Palearctic Collared Lemming (Dicrostonyx torquatus); 40. Unalaska Collared Lemming (Dicrostonyx unalascensis); 41. Gray Red-backed Vole (Craseomys rufocanus); 42. Hokkaido Red-backed Vole (Craseomys rex); 43. Korean Red-backed Vole (Craseomys regulus); 44. Shanxi Red-backed Vole (Craseomys shanseius); 45. Anderson's Red-backed Vole (Craseomys anderson); 46. Smith's Red-backed Vole (Craseomys smithii); 47. Western Red-backed Vole (Myodes californicus); 48. Southern Red-backed Vole (Myodes gapperi); 49. Bank Vole (Myodes glareolus); 50. Tian Shan Red-backed Vole (Myodes centralis); 51. Large-eared Vole (Myodes macrotis); 52. Northern Red-backed Vole (Myodes rutilus); 53. Silver Mountain Vole (Alticola argentatus); 54. White-tailed Mountain Vole (Alticola albicauda); 55. Kashmir Mountain Vole (Alticola montosus); 56. Royle's Mountain Vole (Alticola roylei); 57. Strelzov's Mountain Vole (Alticola strelzovi); 58. Tuva Mountain Vole (Alticola tuvinicus); 59. Gobi Altai Mountain Vole (Alticola barakshin); 60. Lake Baikal Mountain Vole (Alticola olchonensis); 61. Mongolian Mountain Vole (Alticola semicanus); 62. Stoliczka's Mountain Vole (Alticola stoliczkanus); 63. Lemming Mountain Vole (Aschizomys lemminus); 64. Gansu Red-backed Vole (Caryomys eva); 65. Kolan Red-backed Vole (Caryomys inez): 66. Pere David's Red-backed Vole (Eothenomys melanogaster); 67. Yunnan Red-backed Vole (Eothenomys miletus); 68. Sichuan Red-backed Vole (Eothenomys chinensis); 69. Southwest China Red-backed Vole (Eothenomys custos); 70. Black-eared Red-backed Vole (Eothenomys oliton; 71. Yulongxuen Red-backed Vole (Eothenomys proditor); 72. Ward's Red-backed Vole (Eothenomys ward); 73. Hinton's Red-backed Vole (Eothenomys hintoni); 74. Tarquinius Red-backed Vole (Eothenomys tarquinius); 75. Burrowing Vole (Hyperacrius fertilis); 76. Murree Vole (Hyperacrius wynnei). in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
On following pages: 36. Nelson's Collared Lemming (Dicrostonyx nelsoni); 37. Ogilvie Mountains Collared Lemming (Dicrostonyx nunatakensis); 38. Richardson's Collared Lemming (Dicrostonyx richardsoni); 39. Palearctic Collared Lemming (Dicrostonyx torquatus); 40. Unalaska Collared Lemming (Dicrostonyx unalascensis); 41. Gray Red-backed Vole (Craseomys rufocanus); 42. Hokkaido Red-backed Vole (Craseomys rex); 43. Korean Red-backed Vole (Craseomys regulus); 44. Shanxi Red-backed Vole (Craseomys shanseius); 45. Anderson's Red-backed Vole (Craseomys anderson); 46. Smith's Red-backed Vole (Craseomys smithii); 47. Western Red-backed Vole (Myodes californicus); 48. Southern Red-backed Vole (Myodes gapperi); 49. Bank Vole (Myodes glareolus); 50. Tian Shan Red-backed Vole (Myodes centralis); 51. Large-eared Vole (Myodes macrotis); 52. Northern Red-backed Vole (Myodes rutilus); 53. Silver Mountain Vole (Alticola argentatus); 54. White-tailed Mountain Vole (Alticola albicauda); 55. Kashmir Mountain Vole (Alticola montosus); 56. Royle's Mountain Vole (Alticola roylei); 57. Strelzov's Mountain Vole (Alticola strelzovi); 58. Tuva Mountain Vole (Alticola tuvinicus); 59. Gobi Altai Mountain Vole (Alticola barakshin); 60. Lake Baikal Mountain Vole (Alticola olchonensis); 61. Mongolian Mountain Vole (Alticola semicanus); 62. Stoliczka's Mountain Vole (Alticola stoliczkanus); 63. Lemming Mountain Vole (Aschizomys lemminus); 64. Gansu Red-backed Vole (Caryomys eva); 65. Kolan Red-backed Vole (Caryomys inez): 66. Pere David's Red-backed Vole (Eothenomys melanogaster); 67. Yunnan Red-backed Vole (Eothenomys miletus); 68. Sichuan Red-backed Vole (Eothenomys chinensis); 69. Southwest China Red-backed Vole (Eothenomys custos); 70. Black-eared Red-backed Vole (Eothenomys oliton; 71. Yulongxuen Red-backed Vole (Eothenomys proditor); 72. Ward's Red-backed Vole (Eothenomys ward); 73. Hinton's Red-backed Vole (Eothenomys hintoni); 74. Tarquinius Red-backed Vole (Eothenomys tarquinius); 75. Burrowing Vole (Hyperacrius fertilis); 76. Murree Vole ...